2012
DOI: 10.1088/0004-637x/749/1/65
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHEL-ATLAS: TOWARD A SAMPLE OF ∼1000 STRONGLY LENSED GALAXIES

Abstract: While the selection of strongly lensed galaxies with 500µm flux density S 500 > 100 mJy has proven to be rather straightforward (Negrello et al. 2010), for many applications it is important to analyze samples larger than the ones obtained when confining ourselves to such a bright limit. Moreover, only by probing to fainter flux densities is possible to exploit strong lensing to investigate the bulk of the high-z star-forming galaxy population. We describe HALOS (the Herschel -ATLAS Lensed Objects Selection), a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 60 publications
(79 reference statements)
2
86
0
Order By: Relevance
“…A high flux density cut-off (S 500µm > 100 mJy) eliminates a large amount of possible lenses in order to achieve a low contamination rate from unlensed sources (González-Nuevo et al 2012). Lowering the cut-off flux density to 80 mJy was already tested in Wardlow et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…A high flux density cut-off (S 500µm > 100 mJy) eliminates a large amount of possible lenses in order to achieve a low contamination rate from unlensed sources (González-Nuevo et al 2012). Lowering the cut-off flux density to 80 mJy was already tested in Wardlow et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The lensing boost of the effective angular resolution and sensitivity has allowed us to examine in unprecedented details the properties of a typical starburst galaxy when the universe is only 1/7 of its current age. HATLAS12−00 provides a prelude to a golden age of SMG research, as Herschel is unveiling hundreds of strongly lensed SMGs before the mission completes (e.g., González-Nuevo et al 2012;Wardlow et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, if a typical rest-frame spectral energy distribution (SED) of H-ATLAS galaxies can be identified, it can be used to estimate the redshifts directly from Herschel photometric data. Lapi et al (2011) andGonzález-Nuevo et al (2012) showed that the SED of SMM J2135-0102, "The Cosmic Eyelash" at z = 2.3 Swinbank et al 2010) is a good template for  z 1. Comparing the photometric redshift obtained with this SED with spectroscopic measurements for the 36 H-ATLAS galaxies at  z 1 for which spectroscopic redshifts were available González-Nuevo et al (2012) found a median value of…”
Section: H-atlasmentioning
confidence: 99%